Teaching Creativity Across Disciplines at Ontario Universities - Marquis, Elizabeth; Henderson, Jeremy A. (Canadian Journal of Higher Education, 2015)
While a wide variety of publications have suggested that the development of student creativity should be an important objective for contemporary universities, information about how best to achieve this goal across a range of disciplinary contexts is nonetheless scant. The present study aimed to begin to fill this gap by gathering data (via an electronic survey instrument) about how the teaching and learning of creativity are perceived and enacted by instructors in different disciplines at Ontario universities. Results indicated points of both convergence and divergence between respondents from different fields in terms of their understandings of the place of creativity within courses and programs, and in terms of strategies they reported using to enable creativity in their students. We discuss the implications of these findings, including the ways in which the data speak to ongoing debates about the role of disciplines within teaching, learning, and creativity more broadly.